MicroRNA expression profiles of neuron-derived extracellular vesicles in plasma from patients with amyotrophic lateral sclerosis. (24th August 2019) - Katsu, Masataka; Hama, Yuka; Utsumi, Jun; Takashina, Ken; Yasumatsu, Hiroshi; Mori, Fumiaki; Wakabayashi, Koichi; Shoji, Mikio; Sasaki, Hidenao
Highlights: We extracted neuron-derived extracellular vesicles (EVs) in plasma from patients with ALS. MicroRNA expression profiles of neuron-derived EVs were analyzed. A total of 30 differentially-regulated miRNAs were identified in ALS. MicroRNAs in neuron-derived EVs hold promise as potential biomarkers in ALS. Abstract: Circulating microRNAs (miRNAs) in peripheral blood have been extensively investigated as biomarkers for early diagnosis and monitoring of disease progression. However, their cellular origin as well as their link to the pathophysiology, especially neurodegenerative disease, remains largely unknown. In the present study, we isolated neuron-derived extracellular vesicles (EVs) in plasma by immunoaffinity purification and comprehensively analyzed their miRNA expression profiles using microarray. A total of 30 miRNAs were differentially regulated in amyotrophic lateral sclerosis (ALS) plasma relative to healthy control plasma. Gene ontology analysis revealed that biological processes implicated in both up-regulated and down-regulated miRNAs were involved in synaptic vesicle-related pathways. Especially, 4 miRNAs in plasma neuro-derived EVs seemed to be regulated in the similar manner as those in formalin-fixed paraffin-embedded motor cortex samples from ALS patients. The target genes for the 4 miRNAs partly overlapped in STX1B, RAB3B, and UNC13A genes. UNC13A has been reported to be associated with increased odds of sporadic ALS in multiple genome-wide association studies. Our data suggest that miRNAs extracted from neuron-derived EVs in plasma reflect miRNA alterations in the brain as potential biomarkers of ALS.